Pelatihan CorelDRAW untuk Membuat Desain Logo di SMK Ibrahimy 1 Sukorejo Situbondo - Zaehol Fatah; Ach Yusril Ihza Mahendra (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Students at SMK Ibrahimy 1 Sukorejo Situbondo currently possess limited skills in logo design using the CorelDRAW application. This community service activity aimed to enhance participants' knowledge and skills in creating vector-based logo designs using CorelDRAW. The training was attended by 30 students and conducted through a combination of lectures, demonstrations, hands-on practice, discussions, and mentoring. Evaluation was carried out via observation during the activity, assessment of the logo designs produced, and the distribution of participant satisfaction questionnaires. The evaluation results indicated an average satisfaction rate of 90.6%, with the "usefulness" aspect receiving the highest score at 94%. Furthermore, participants demonstrated improved understanding of basic logo design concepts and increased proficiency in using CorelDRAW's fundamental features. Thus, the training was effective in enhancing the participants' understanding and basic skills in logo design using CorelDRAW.